2009
DOI: 10.1073/pnas.0900740106
|View full text |Cite
|
Sign up to set email alerts
|

Solution to the problem of the poor cyclic fatigue resistance of bulk metallic glasses

Abstract: The recent development of metallic glass-matrix composites represents a particular milestone in engineering materials for structural applications owing to their remarkable combination of strength and toughness. However, metallic glasses are highly susceptible to cyclic fatigue damage, and previous attempts to solve this problem have been largely disappointing. Here, we propose and demonstrate a microstructural design strategy to overcome this limitation by matching the microstructural length scales (of the sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
39
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(41 citation statements)
references
References 47 publications
2
39
0
Order By: Relevance
“…10. This is a similar result to what has been shown in quasistatic fracture toughness tested samples 18 and fatigue samples 20 of DH1. Since the specimen size is small, both in terms of thickness as well uncracked ligament length, a plastic hinge develops and the data obtained are no longer valid in the context of fracture mechanics.…”
Section: Micromechanisms Of Crack Growthsupporting
confidence: 91%
See 2 more Smart Citations
“…10. This is a similar result to what has been shown in quasistatic fracture toughness tested samples 18 and fatigue samples 20 of DH1. Since the specimen size is small, both in terms of thickness as well uncracked ligament length, a plastic hinge develops and the data obtained are no longer valid in the context of fracture mechanics.…”
Section: Micromechanisms Of Crack Growthsupporting
confidence: 91%
“…A number of factors such as the angle of crack incidence, the elastic mismatch across the interface, and the ratio of interfacial toughness determine the path of the crack. 20 It is inferred from scanning electron micrographs that at higher incidence angles the crack penetrates through the dendrites, while at lower incidence angles the crack gets deflected and passes through interface of dendrites and matrix. Fractographs obtained from the samples that fractured into two pieces are shown in Fig.…”
Section: Micromechanisms Of Crack Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…While Vitreloy 105 shows probably the highest strength-normalized fatigue endurance of ~0.24 (Naleway et al, 2013), which is also comparable to some high-strength steels, many attempts have been taken to improve the fatigue performance of BMGs. For example, Launey et al (2009) developed glass matrix composites with microstructural length scales of the second phase according with mechanical crack length scales (Launey et al, 2009). A retarded growth of small flaws acting as preferential crack initiation sites was achieved, and subsequent failure by single shear band opening could be impeded.…”
mentioning
confidence: 99%
“…By introducing a second phase in form of crystalline dendrites and by matching microstructural length scales ͑i.e., interdendritic spacing͒ to the mechanical length scales ͑i.e., critical crack size for failure͒, nonlocalized plasticity in metallic glasses can be enhanced significantly. [5][6][7] Indeed, the recent development of in situ bulk metallic glass-matrix composites has shown that provided this phase acts to arrest shear-band propagation over appropriate size scales, [8][9][10] the problems of poor ductility, toughness, and fatigue resistance can be mitigated.…”
mentioning
confidence: 99%